2017
DOI: 10.4314/gjds.v14i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Economic Efficiency of Maize Production in Northern Ghana

Abstract: This study used the stochastic frontier model to examine the technical, allocative and economic efficiency of maize production in northern Ghana using cross-sectional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 19 publications
18
37
0
Order By: Relevance
“…This is not surprising as land is not a major limitation to production in Northern Ghana. This result corresponds to that of Abdulai et al [32] who found land, seeds, and agro-chemicals to have positive significant elasticities for maize in Northern Ghana. As one can note, fertilizer input and agro-chemicals are likely to stimulate production to a lower extent than land and seed inputs.…”
Section: Production Function Of Soybean In Northern Ghanasupporting
confidence: 90%
“…This is not surprising as land is not a major limitation to production in Northern Ghana. This result corresponds to that of Abdulai et al [32] who found land, seeds, and agro-chemicals to have positive significant elasticities for maize in Northern Ghana. As one can note, fertilizer input and agro-chemicals are likely to stimulate production to a lower extent than land and seed inputs.…”
Section: Production Function Of Soybean In Northern Ghanasupporting
confidence: 90%
“…Farrell (1957) identified not only the concept of having an actual measure of efficiency in a production system (such as a farming operation), but also outlined the difficulties in developing this estimate for very complex processes. For the study reported here, a stochastic frontier production function model was preferred as this best captures random effects associated with outliers, and has been widely used as the preferred method in studies of agricultural production systems in many countries (Abdulai et al, 2013;Ahmad and Bravo-Ureta, 1996;Thiam et al, 2001). We used the same equation as given in Abdulai et al (2013), and similarly used the computer program FRONTIER Version 4.1 (Coelli, 1996) to estimate TE based on a Cobb-Douglas production function (Aigner and Chu, 1968) using the data collected in each year.…”
Section: Technical Efficiencymentioning
confidence: 99%
“…Best practice recommendations for farmers are based on extensive field trials, which concentrate on producing as high yield as possible from a given set of inputs. The ability of farmers to improve yields and optimize economic returns depends on efficient farm practices, and technical efficiency (TE) is a commonly used measure of farm efficiency (Abdulai et al, 2013;Goyal and Suhag, 2003;Singh, 2007;Thiam et al, 2001). TE is defined as the ability of a decision-making unit (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the drivers of technical efficiency identified in previous studies, maize farmers continue to experience low yields [27] depicting the failure of recommendations of previous studies to help address the productivity and efficiency challenges farmers have faced over the years. By way of literature review, [2] employed the stochastic frontier analysis procedure and estimated the technical efficiency of maize farmers in Northern Ghana to be 74%. The study concluded that their technical efficiencies were positively influenced by agricultural mechanization, experience and gender.…”
Section: Introductionmentioning
confidence: 99%